2022
DOI: 10.1371/journal.pone.0270814
|View full text |Cite
|
Sign up to set email alerts
|

Severe influenza A in a Tunisian ICU sentinel SARI centre: Epidemiological and clinical features

Abstract: Introduction Influenza A virus infection is a contagious acute respiratory infection which mostly evolves in an epidemic form, less frequently as pandemic outbreaks. It can take a severe clinical form that needs to be managed in intensive care unit (ICU). The aim of this study was to describe the epidemiological and clinical aspects of influenza A, then to determine independent predictive factors of ICU mortality in Abderrahmen Mami hospital, Ariana, Tunisia. Methods It was a single-center study, including a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Differences we found were that patients hospitalized after 2022 were younger (63-year-old median age Before-2020 vs. 59.5-year-old median age After-2022), and asthma and obesity were more prevalent in this population, but asthma was still less frequent than in the 2009 flu pandemic caused by the AH1N2pdm09 strain [ 19 ]. The prevalence of obesity increased to 25% of hospitalized patients After-2022 in this database, which is more than other studies which addressed this [ 20 , 21 ]. The study groups were also very similar in the rates of severe cases (64.7% cases Before-2022, 62.69% After-2022).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Differences we found were that patients hospitalized after 2022 were younger (63-year-old median age Before-2020 vs. 59.5-year-old median age After-2022), and asthma and obesity were more prevalent in this population, but asthma was still less frequent than in the 2009 flu pandemic caused by the AH1N2pdm09 strain [ 19 ]. The prevalence of obesity increased to 25% of hospitalized patients After-2022 in this database, which is more than other studies which addressed this [ 20 , 21 ]. The study groups were also very similar in the rates of severe cases (64.7% cases Before-2022, 62.69% After-2022).…”
Section: Discussionmentioning
confidence: 68%
“…The prevalence of pneumonia with infiltrates of this study is lower than in other studies in the literature. Amira Jamoussi et al found that pneumonia with infiltrates was present in 85% of their subjects [ 20 ], but their study was focused only on patients with severe acute respiratory infection. Kelsey M Sumner et al [ 22 ] also identified a higher percentage of pneumonia in their group, but the definition of pneumonia was not provided.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed that the rate of positive urine tests for IAV was 58% in patients infected with IAV ( Lowry et al., 2023 ). Importantly, the 2009 pandemic was associated with significant extrapulmonary complications ( Lee et al., 2011 ), among which IAV-induced acute kidney injury (IAV-AKI) was related to increased mortality ( Abdulkader et al., 2010 ; Martin-Loeches et al., 2011 ; Nin et al., 2011a ; Thakkar and Golestaneh, 2021 ), and this trend is continuing in IAV-AKI ( Ersoy et al., 2021 ; Hsu et al., 2022 ; Jamoussi et al., 2022 ). Yet, the pathophysiology of IAV-AKI is incompletely understood ( Joannidis and Forni, 2011 ; Watanabe, 2013 ).…”
Section: Introductionmentioning
confidence: 99%